ORGANIZATIONAL FUNDAMENTALS OF IMPLEMENTATION OF STATE POLICY IN THE FIELD OF GREEN TOURISM IN UKRAINE - Darmostuk D.Н. (Pressing Problems of Public Administration, 2017)
The organizational principles of realization of the state policy in the field of green tourism in Ukraineare analyzed, the key functions of the subjects of tourist activity are defined.